Mental health in public safety personnel with workplace injuries requiring surgery: a longitudinal population-wide administrative data study in Manitoba, Canada - Tracie O Afifi; Jitender Sareen; Dan Chateau; Alyson Mahar; Jordan Nantais; James Bolton; Allen Kraut; Sarvesh Logsetty; Thomas Turgeon; Brenda Comaskey; Justin Gawaziuk; Rae Spiwak; et al. (BMJ Open)
Objectives Public safety personnel (PSP) are responsible for ensuring the safety and security of communities, often putting their own lives and well-being at risk by performing dangerous and demanding work. As a result, these workers are particularly vulnerable to workplace-related physical and mental traumatic injuries. Research is needed to understand the mental health of PSP following traumatic physical injury to inform effective prevention programmes and interventions. The objective of this study was to investigate whether PSP with traumatic physical workplace injuries requiring surgery with anaesthetic have higher post-injury rates of mental disorders compared with the general population with similar non-workplace injuries.Design Retrospective longitudinal cohort study.Setting Population-based study using linked anonymised administrative data for PSP and the general population in Manitoba, Canada.Participants This study compared two groups hospitalised for a traumatic physical injury requiring surgery with anaesthetic between 1 January 2002 and 31 December 2018: (1) PSP (n=293) injured in the workplace and matched 1:5 on sex, age, geographical region and surgical procedure code with (2) individuals in the general population (GenPop) injured outside the workplace (no Workers Compensation Board claim) (n=1198).Primary and secondary outcomes and measures As planned in the study protocol, the prevalence of mental disorders including anxiety, depression and substance use was measured in the cohorts 2 years pre- and post-injury.Results This study found an elevated unadjusted risk of depression in PSP compared with the general population in the 2 years post-injury, adjusting for pre-injury mental health (rate ratio, 1.49; 95% CI, 1.02 to 2.17; p<0.0001). After adjusting, there were no significant differences in rates between the two cohorts; however, the significant group × care interaction term for depression suggests a greater risk for PSP compared with GenPop over time.Conclusions Our findings indicate that, compared with a matched cohort, PSP have an increased risk of depression from the pre-injury to post-injury period following a traumatic physical workplace injury. PSP have a unique mental health trajectory following workplace injury that should be considered when developing rehabilitation strategies for this important population.